Drug-related stigma among people who inject drugs – development and validation of the drug use stigma scale (DUSS) - Robin A. Pollini; Catherine E. Paquette; Brandon Irvin; Jennifer L. Syvertsen; Christa L. Lilly (PLoS ONE, 2025)
Drug use is a highly stigmatized behavior, and drug-related stigma is a key driver of behavioral risk, lower health care utilization, and associated adverse health outcomes among people who inject drugs (PWID). While instruments exist for measuring drug-related stigma, their applicability to community-based PWID across multiple stigma types (enacted, anticipated, internalized) and settings (health care, society, family) is limited, as most were developed using treatment-based samples and all were developed in urban populations. This study sought to develop a Drug Use Stigma Scale (DUSS) that addresses these limitations. We developed an initial list of 39 items based on literature review and qualitative interviews (N = 27) and three focus groups (N = 28) with PWID recruited from syringe services programs and via peer referral in two predominantly rural West Virginia counties. The scale items were administered in a survey to 336 PWID recruited from the same two counties divided into development and validation samples. Responses to the 39-item scale went through a multidimensional refinement process, including examination of internal consistency, Confirmatory Factor Analysis (CFA), and a three-factor CFA based on stigma setting. Next, a set of final measurement CFAs were conducted. Finally, the resulting scale was examined for criterion-related concurrent validation. The final DUSS consisted of 16 items with excellent fit statistics for the development sample: SRMR: 0.03, RMSEA: 0.09, GFI: 0.92, CFI: 0.96, NFI: 0.94. Fit attenuated but remained satisfactory for the validation sample. DUSS scores were significantly associated with increased odds of not seeking healthcare when needed (OR: 1.47, p = 0.001; OR: 1.61, p < 0.0001) after controlling for gender and age. Thus, the resulting scale, the DUSS, demonstrates strong validity and internal reliability across multiple stigma mechanisms and settings in a rural population, making it a valuable tool for broadly assessing drug-related stigma and related intervention effectiveness among PWID.